INFLUENCE GIVING INFUSION OF LEMON WATER (Citrus limon) AND CUCUMBER (Cucumissativus L) ON SUFFERER HYPERTENSION IN REGION WORK PUBLIC HEALTH CENTER PUUWATU CITY KENDARI - Rofiqoh, Rofiqoh; Van Gobel, Sri Yunanci (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Hypertension is one of the silent killer diseases that causes the iceberg phenomenon. The prevalence of hypertension increases with age. If this pathological condition does not get treatment quickly and early, it will exacerbate the risk. Based on the results of Riskesdas (2018) in Indonesia the prevalence of hypertension was 31.7%. The prevalence of Hypertension for Southeast Sulawesi Province based on the results of Riskesdas in 2007 was 31.7%, Riskesdas in 2013 decreased to 25% and in Riskesdas in 2018 it rose to 31%. Data on the health profile of Puuwatu Public Health Center, Kendari City, hypertension in adults (20-44 years) in the last 3 years showed that in 2014 there were 284 cases, in 2015 there were 222 cases, in 2016 increased to 419 cases and in 2017 to 498 cases. Infused water is water that is mixed with fruit and then allowed to stand for a few hours until the juices come out . To determine the effect of Infusion of Fruit and Vegetable Water (cucumber and lemon) on Hypertension Patients in the Work Area of Puuwatu Health Center, Kendari City. This type of research is Quasi experimental using a two group pre-post test design with control with a survey approach. This research was conducted on November 5, 2020 to January 29, 2021. The design of this study was to provide Infused Water of fruits and vegetables (cucumber and lemon) to hypertension patients who were previously checked for blood pressure and then given an intervention in the form of giving Infused Water of fruits and vegetables (cucumber 100 g) and 50 grams of lemon plus 250 ml of mineral water) 1 time a day for 8 consecutive days. Blood pressure was checked 4 times after giving Infused Water fruit and vegetable. The sample is all adults who suffer from hypertension totaling 64 people. The sampling technique Purposive sampling. Blood pressure before and after the intervention by giving Cucumber and Lemon Infused Water for 8 days and measuring blood pressure 4 times (every 2 days) that the mean systolic blood pressure before and after the intervention for the case group was 144.4575 mgHg and the control group was 152.155 mgHg and diastolic blood pressure before and after the intervention, the mean for the case group was 90.9375 mgHg and the control group was 96.335 mgHg. The results of independent t-test in cases and controls systolic blood pressure p value = 0.339 ( 0.05) while diastolic p value = 0.374 ( 0.05), that there is no significant difference in systolic and diastolic blood pressure in the two sample groups .then averaged were . the diastolic variable obtained p value = 0.17 (0.05) so it can be said that for systolic and diastolic blood pressure there is an effect.